What is Risk to Managers? - Jeppe Christoffersen; Felix Holzmeister; Thomas Plenborg (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2021)
We systematically examine which characteristics of a business opportunity - such as the likelihoods of potential gains and losses - affect managers' perception of risk and attractiveness. In an online experiment with a sample of 4,287 managers from smalland medium-sized enterprises in Denmark, we present participants with a hypothetical investment prospect in a business context, and elicit their perception of risk associated with the project and their perception of the investment's attractiveness. The experimental data is merged with a set of background variables on the company, which allows controlling for firm-specific effects. We find that risk perception is driven by the likelihood and the return associated with the worst-case scenario as well as the size of the required investment. Managers' perception of attractiveness is affected not only by the worst-case scenario but also by the characteristics of the base-case and the best-case outcomes. Furthermore, we provide evidence that managers' perception of the project's attractiveness is significantly affected by their individual-level risk preferences and the interaction effect with risk perception. This implies that not only the characteristics of the different scenarios but also individuals' risk preferences play an important role when assessing the attractiveness of a business opportunity.
Keywords: 330; risk perception; risk preferences; attractiveness of investment project; business opportunity